PEMBUATAN PIGMENT TITANIUM DIOKSIDA (TIO2) DARI ILMENITE (FETIO3) SISA PENGOLAHAN PASIR ZIRCONDENGANPROSES BECHER - Mohammad Taufik Mohar; Dewi Fatmawati; Setia Budi Sasongko (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Indonesia is a country that has a lot of Ilmenite (FeTiO3), but as yet only plays the role of an exporter of this important raw material. The exact conditions for processing Ilmenite into products for sand proficiency levels as well as industrial raw material pigments are not yet known. Improved grade of titanium dioxide as a separation process should be supported by research on natural raw material sources that can be used. One raw material is waste zircon sand in Central Kalimantan (Borneo), which contains 80-90% of Ilmenite. The purpose of this research was to determine the effect of aeration time and concentration of salt catalyst (NH4Cl) on the transformation rate of iron (Fe) into iron oxide (Fe2O3), where iron oxide and titanium dioxide was separated by acid leaching process to produce pure titanium dioxide. The titanium oxide purification process adopted from Becher process which is the process of oxidation, reduction, aeration, leaching, stripping, and calcination. In this experiment, the fixed variables used were time of oxidation and reduction of 3 hours and time of calcination of 3 hours. The changing variables used were aeration time of 2, 4, 6, and 8 hours; and concentration of salt catalyst (NH4Cl) of 1%, 2%, and 3%. XRD (X-ray Diffraction) qualitative analysis and GSAS (General Structure Analysis System) quantitative analysis on the results showed an increase in TiO2 content on all the variables. The process of increasing TiO2 content at a variable of 1% NH4Cl gave the best result. The greater the concentration of NH4Cl catalyst, the smaller the TiO2 increase. The best time for improving the grade of TiO2 was 4 hours, proven by a very effective transformation of Fe into Fe2O3. The result of research gave a potential concentration of titanium dioxide was 45.86% with aeration process time of 4 hoursand NH4Cl concentration of 1%.